2016
DOI: 10.3390/su8090883
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Thermal and Lighting Energy Performance of Shading Devices on Kinetic Façades

Abstract: Abstract:In order to evaluate the thermal and lighting energy performance of a kinetic façade using external movable shading devices, it is important to consider the operation of the shading devices since it can influence the performance significantly. This study proposes a calculation methodology which assesses the performance of the movable shading devices with the consideration of the movements of the shading devices. Calculation methods were derived by which solar heat gain, lighting energy requirement, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…The results of the research allow us to confirm that it is possible to define the factors controlling the movement mechanism and features related to morphological design of the façade, the type of plant implemented, and the material selection, which are used as parameters that should be taken into account during the preliminary design phase of the kinetic green façade. The obstruction index, light transmittance, and exposure coefficient of the shading devices are the features related to thermal, lighting, and energy performance of kinetic façade shading devices [37]. These features are dependent on the morphological design of the system and material type.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the research allow us to confirm that it is possible to define the factors controlling the movement mechanism and features related to morphological design of the façade, the type of plant implemented, and the material selection, which are used as parameters that should be taken into account during the preliminary design phase of the kinetic green façade. The obstruction index, light transmittance, and exposure coefficient of the shading devices are the features related to thermal, lighting, and energy performance of kinetic façade shading devices [37]. These features are dependent on the morphological design of the system and material type.…”
Section: Discussionmentioning
confidence: 99%
“…He identified that the radiation value at which most users operated the blinds was 233 W/m 2 . Lee et al [46] suggested a value of 200 W/m 2 in a study about the evaluation of thermal and lighting energy performance of shading devices on kinetic facades for the climate of Dubai (UAE). Wankanapon [47] found a value of 189 W/m 2 for a white roller shade allowing to save cooling energy from 21 to 27% for the climate of Minneapolis (USA).…”
Section: Sub-variantsmentioning
confidence: 99%
“…Em se tratando de sistemas de proteção solar, destacam-se alguns trabalhos com abordagens capazes de considerar os critérios térmicos e luminosos simultaneamente, como Lima, Bittencourt e Caram (2013) e Manzan (2014), que estudam a relação da geometria dos dispositivos de controle solar no desempenho do ambiente interno, e Lee et al (2016) e Carletti et al (2016), que avaliam a performance termoluminosa de sistemas de proteção solar automatizados. De modo geral, esses trabalhos evidenciam a complexidade de conciliar os aspectos térmicos e luminosos no desenvolvimento de sistemas de proteção solar.…”
Section: Introductionunclassified